2018
DOI: 10.1016/j.aninu.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Non-antibiotic feed additives in diets for pigs: A review

Abstract: A number of feed additives are marketed to assist in boosting the pigs' immune system, regulate gut microbiota, and reduce negative impacts of weaning and other environmental challenges. The most commonly used feed additives include acidifiers, zinc and copper, prebiotics, direct-fed microbials, yeast products, nucleotides, and plant extracts. Inclusion of pharmacological levels of zinc and copper, certain acidifiers, and several plant extracts have been reported to result in improved pig performance or improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
209
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(221 citation statements)
references
References 220 publications
2
209
0
10
Order By: Relevance
“…Introduction The reduction of antimicrobial growth promotors (AGP) increases pathogenic bacterial challenge in weaned pigs particularly in a poorer sanitary environment. Previous reports have indicated that dietary xylo-oligosaccharides (XOS) stimulates beneficial bacteria in the intestinal tract enhancing the immunity of weaner pigs (Liu et al, 2018). The hypotheses tested in this study were (1) pigs housed in a poorer sanitary condition will increase pro-inflammatory cytokine production, and (2) combined supplementation of xylo-oligosaccharides (XOS) and xylanase will reduce proinflammatory cytokine production via stimulation of fibre fermenting microbiota when compared to a mannanoligosaccharide (MOS) or fructo-oligosaccharide (FOS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction The reduction of antimicrobial growth promotors (AGP) increases pathogenic bacterial challenge in weaned pigs particularly in a poorer sanitary environment. Previous reports have indicated that dietary xylo-oligosaccharides (XOS) stimulates beneficial bacteria in the intestinal tract enhancing the immunity of weaner pigs (Liu et al, 2018). The hypotheses tested in this study were (1) pigs housed in a poorer sanitary condition will increase pro-inflammatory cytokine production, and (2) combined supplementation of xylo-oligosaccharides (XOS) and xylanase will reduce proinflammatory cytokine production via stimulation of fibre fermenting microbiota when compared to a mannanoligosaccharide (MOS) or fructo-oligosaccharide (FOS).…”
Section: Resultsmentioning
confidence: 99%
“…Phytomolecules are used by the plant to communicate, to attract dispersal vectors or to defend itself from attack, rather than being involved in the primary growth or reproduction of the plant. These extracts have been shown to improve animal health through the enhancement of immune function, alteration of the gut microbiota and direct suppression of pathogens (Liu et al, 2018). We hypothesise that the inclusion of phytomolecules in the diet of weaner pigs will enhance post-weaning performance.…”
Section: Figurementioning
confidence: 99%
“…The effects of adding yeast products to diets for pigs are not fully understood, but it is believed that yeast products may have a number of positive effects if added to pig diets and there is some evidence that yeast products can be used as partial or fully alternatives to antibiotic growth promoters. The benefits of intestinal health and immunomodulatory effects of yeast cells are important and represent the most likely benefits of supplementing pig diets with yeast (Liu et al ). Live yeast, finely ground live yeast and yeast fermentation products may lead to increased villus heights and villus‐to‐crypt ratios (Bontempo et al ; Shen et al ; Jiang et al ).…”
Section: Probiotic Yeast For Pigsmentioning
confidence: 99%
“…Concerns and legislative actions around antibiotic use in food animals are leading to an increase in the search for tools to counter pathogens. Promoting immune development or expression in young animals is one example, which also tends to improve growth [10]. A recent addition to vaccines, therapeutic drugs, and immune enhancers is medium-chain fatty acids (MCFAs), especially saturated MCFAs with 6-12 carbon-long chains, which have demonstrated positive benefits as feed additives by improving animal health, production, and feed digestibility [11].…”
Section: Introductionmentioning
confidence: 99%